Oral Health Symptoms and Smokeless Tobacco Use Among Outpatients in Bangladesh: Insights from a Cross-Sectional Study - Noor, Ashek Elahi; Kabir, Russell (Queeva Publishing, 2025)
Background: In low-income nations like Bangladesh, the use of smokeless tobacco (SLT) is common and linked to major oral health problems such tooth stains, cavities, and precancerous lesions. Methods: At the evening OPD of Sapporo Dental College and Hospital in Dhaka, a descriptive cross-sectional study was carried out between April and October 2023. 400 people were polled using a standardized questionnaire and purposive sampling. Logistic regression and descriptive statistics were used to analyze the data. Results: The majority of responders (84.75%) were men, and the age group of 35–54 years old accounted for 39.5% of the total. The use of SLT was more common in older people and teenagers. The most often reported oral complaints were poor breath (75%) and dental stains (90.75%). SLT use was found to be substantially correlated with peer influence, decreased perceived severity and benefits, and age ≥14 years (OR = 6.58), according to logistic regression. Just 29.2% of respondents said they intended to stop after seeing the health warnings. Conclusion: SLT use is very common among adults in Dhaka who visit the dental outpatient department, despite their lack of knowledge about the health hazards. In order to enhance public health outcomes in Bangladesh, the findings emphasize the necessity of integrated oral health and tobacco cessation initiatives in community clinics and educational settings.